Five‐Year Healthcare Utilization and Costs Among Lower‐Risk Drinkers Following Alcohol Treatment. (7th October 2013) - Kline‐Simon, Andrea H.; Weisner, Constance M.; Parthasarathy, Sujaya; Falk, Daniel E.; Litten, Raye Z.; Mertens, Jennifer R.
<x xml:space="preserve">Abstract</x> Background Lower‐risk drinking is increasingly being examined as a treatment outcome for some patients following addiction treatment. However, few studies have examined the relationship between drinking status (lower‐risk drinking in particular) and healthcare utilization and cost, which has important policy implications. Methods Participants were adults with alcohol dependence and/or abuse diagnoses who received outpatient alcohol and other drug treatment in a private, nonprofit integrated healthcare delivery system and had a follow‐up interview 6 months after treatment entry (N = 995). Associations between past 30‐day drinking status at 6 months (abstinence, lower‐risk drinking defined as nonabstinence and no days of 5+ drinking, and heavy drinking defined as 1 or more days of 5+ drinking) and repeated measures of at least 1 emergency department (ED), inpatient or primary care visit, and their costs over 5 years were examined using mixed‐effects models. We modeled an interaction between time and drinking status to examine trends in utilization and costs over time by drinking group. Results Heavy drinkers and lower‐risk drinkers were not significantly different from the abstainers in their cost or utilization at time 0 (i.e., 6 months postintake). Heavy drinkers had increasing odds of inpatient (p < 0.01) and ED (p < 0.05) utilization over 5 years compared with abstainers. Lower‐risk drinkers and abstainers did not significantly differ in their service use in any category over time. No differences were found in changes in primary care use among the 3 groups over time. The cost analyses paralleled the utilization results. Heavy drinkers had increasing ED (p < 0.05) and inpatient (p < 0.001) costs compared with the abstainers; primary care costs did not significantly differ. Lower‐risk drinkers did not have significantly different medical costs compared with those who were abstinent over 5 years. However, post hoc analyses found lower‐risk drinkers and heavy drinkers to not significantly differ in their ED use or costs over time. Conclusions Performance measures for treatment settings that consider treatment outcomes may need to take into account both abstinence and reduction to nonheavy drinking. Future research should examine whether results are replicated in harm reduction treatment, or whether such outcomes are found only in abstinence‐based treatment.